Hakikat Bersyukur Perspektif Al-Qur’an - Siti Hajar; Toto Santi Aji (AL-MUFASSIR, 2021)
The present study aims to discover the essence of syukur in Al-Qur’an perspective. This study employs a qualitative study by gathering object of the study in form of written sources such as Al-Qur’an, interpretation books, and Al-Qur’an translation books. This study employs an inductive method by gathering all the verses and interpretation explanations and ultimately portraying conclusions regarding the meaning and nature of gratitude (syukur). The findings indicate that gratitude (syukur) is an acknowledgement of the blessing from the Giver (mun’im) through obedience. Gratitude is also a manifestation of thankfulness for Allah’s blessings. An act of gratitude will provide benefits for the committer where Allah will give His endless blessings. Gratitude can also be realized by a speech (bi al-lisan) without using verbal but to only praise Allah, bodies (bi al-badan) in which without using entire body structure except to obey Him, heart (bi al-qalb) in which without burdening heart but to only to praise Him through dhikr (prayers), and wealth (bi al-mal) in which not spending wealth except only on the path of pleasure and love for Him.